Analysis of Gas Station Financial Management to Prevent Fraud and Anticipate the Impact of Revenue Fluctuations - Chylvia Febelia Elvionita; Theresia Dwi Hastuti (UNIVED Press, 2024)
The aim of this research is to explore how management can prevent and control fraud and also anticipate the impact of fluctuations in ABC gas station revenues. The research methodology employed in this study is a qualitative approach with a case study conducted at ABC Gas Station. Data was gathered through interviews with the head of the finance department, administrative personnel, supervisors, managers, the director of ABC Gas Station, and the SPI Foundation team. The collected data was then analyzed and further developed utilizing the Triangle Fraud Theory, consisting of pressure, opportunity, and rationalization. By comprehending these factors, ABC Gas Station can pinpoint potential areas susceptible to fraudulent activities and implement appropriate controls to prevent them. This study provides valuable insights into the financial management practices at ABC Gas Station, offering actionable recommendations to strengthen operational integrity and navigate the challenges posed by fraud and revenue fluctuations. By implementing these suggestions, gas stations can ensure more robust financial management and secure long-term sustainability in a competitive market. This research significantly advances the understanding of financial management within gas stations by conducting a comprehensive evaluation of its susceptibility to fraudulent activities, particularly in light of past incidents. It uniquely combines financial analysis with the Triangle Fraud Theory to comprehensively assess the weaknesses in the financial management system and the justifications behind fraudulent actions. This integration of financial evaluation and fraud theory represents a fresh perspective in addressing financial integrity in gas station businesses.